Investigation of the interaction of anthraquinones of Cassia occidentalis seeds with bovine serum albumin by molecular docking and spectroscopic analysis: Correlation to their in vitro cytotoxic potential. (November 2015) - Panigrahi, Gati Krushna; Suthar, Manish K.; Verma, Neeraj; Asthana, Somya; Tripathi, Anurag; Gupta, Shailendra K.; Saxena, Jitendra K.; Raisuddin, S.; Das, Mukul
Abstract: Anthraquinones (AQs) of the Cassia occidentalis (CO) seeds like Rhein, Emodin, Aloe-emodin, Chrysophanol, Physcion are known to contribute to the etiology of hepatomyoencephalopathy in children. The present study was carried out to investigate the binding affinity of these AQs with serum albumin, as this protein is mainly involved in the bio-distribution of xenobiotics. Initially, molecular docking was carried for the five AQ ligands with bovine serum albumin (BSA) both by AUTODOCK and CDOCKER docking tools. Subsequently, the binding affinity and mechanism of interaction of these AQs with BSA was studied by fluorescence and UV–visible spectroscopy. Additionally, in vitro cytotoxicity studies of these AQs were carried out in rat primary hepatocytes and HepG2 cells. Results both from molecular docking and fluorescence spectroscopic studies suggest that the interaction energy and binding affinity of above AQs with BSA is in the following order, i.e. Rhein > Emodin > Aloe-emodin > Chrysophanol > Physcion. Interestingly, the observed cytotoxicity of the five AQs in rat primary hepatocyte and HepG2 cells were found to fall in line with the above order. Rhein showing highest toxicity among the AQs showed highest binding affinity to BSA, whereas chrysophanol & physcion, being less toxic exhibited minimal affinity to BSA. Hence, these studies indicate that toxicity of AQs of CO seeds are directly proportional to the protein binding affinity, which may be responsible for the death of children and cattle fed of CO seeds. Graphical abstract: Highlights: Rhein is the most toxic anthraquinone in HepG2 cells and rat primary hepatocytes. Rhein has the maximum binding affinity to bovine serum albumin. Rhein has the minimum CDOCKER interaction energy. Cytotoxicity of anthraquinones are proportional to their protein binding affinity.